CITRA TOKOH WANITA MUSLIMAH DALAM NOVEL-NOVEL KARYA ASMA NADIA - Putri, Prihatini; Hayati, Yenni; Nasution, Bakhtaruddin (Universitas Negeri Padang, 2017)
The purpose of this study is to describe the image of the Muslim woman character in the novel Surga yang Tak Dirindukan, Assalamualaikum Beijing, and Jilbab in Love written by Asma Nadia. This was a qualitative research with descriptive method based on content analysis. Object of this study was novel Surga yang Tak Dirindukan, Assalamualaikum Beijing, and Jilbab in Love written by Asma Nadia. Data analysis was done by (1) classifying the data associated with the image of the Muslim woman, (2) interpreting the data associated with the image of Muslim women, (3) analyzing and inventorying data associated with the image of Muslim women, (4) concluding the data. The findings of this research indicate that the image of the Muslim women in the novel Surga yang Tak Dirindukan, Assalamualaikum Beijing, and Jilbab in Love written by Asma Nadia is women who are honest and keep his verbal, patient and sincere women, women who are fasting and keep her prayer, women who maintain honor and views, the women who remember Allah/God remembrance, and qanitaat.Keywords: image of woman, moeslimah, Asma Nadia, novel